2002
DOI: 10.1097/00005392-200207000-00098
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Slow Wave and Contractile Activity of the Guinea Pig Prostate

Abstract: Movement of the contents of the peripheral prostatic acini into the minor and major prostatic ducts is likely to occur via spontaneous contractions triggered by myogenic slow wave activity in the stromal wall. By analogy with the intestine and urethra prostatic interstitial cells may well act as the pacemaker for prostatic slow waves as well as form an intercellular communication network interacting with the intrinsic nerves and stromal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(88 citation statements)
references
References 26 publications
3
85
0
Order By: Relevance
“…Cajal [1] saw these cells as interstitial neurons. Güldner et al [40] demonstrated a system of interconnected ''fibroblasts'' in the stroma of duodenal villi containing thick and thin contractile filaments. The organization (Fig.…”
Section: The Myofibroblasts (Or Myoid Cells) Of the Intestinal Villimentioning
confidence: 99%
See 1 more Smart Citation
“…Cajal [1] saw these cells as interstitial neurons. Güldner et al [40] demonstrated a system of interconnected ''fibroblasts'' in the stroma of duodenal villi containing thick and thin contractile filaments. The organization (Fig.…”
Section: The Myofibroblasts (Or Myoid Cells) Of the Intestinal Villimentioning
confidence: 99%
“…Further ultrastructural studies, and further investigations into the relationship of these cells to other cells in the pancreas, in particular the intrinsic nerves and smooth muscle cells, are eagerly awaited. Richard Lang and co-workers reported on c-kit positive interstitial cells in the guinea pig prostate that formed a network of interconnecting cells with associations with stromal smooth muscle cells and varicose axon bundles [40]. Further experimentation is underway to ascertain a possible origin of spontaneous slow waves in the guinea pig prostate interstitial cells [40].…”
Section: Interstitial Cells In Glandsmentioning
confidence: 99%
“…In a series of recent papers, ICC-like cells have been claimed to occur in other organs: vas deferens [25], urethra [26][27][28], bladder [29][30][31][32][33], ureter [34,35], uterus [36,37], blood vessels [38][39][40], lymphatics [41], prostate [42,43], penis [44], mammary gland [45] and pancreas [46].…”
Section: Introductionmentioning
confidence: 99%
“…The role of ICCs in the human urinary tract has not been finally defined, but they probably act similarly to the widely known cells of Cajal of the gastrointestinal tract, which is suggested by studies carried out on animal models [21,40,41].…”
mentioning
confidence: 99%